Modelling, Detection And Exploitation Of Lexical Functions For Analysis. - Schwab, Didier; Lafourcade, Mathieu (2007)
Lexical functions (LF) model relations between terms in the lexicon. These relations can be knowledge about the world (Napoleon was an emperor) or knowledge about the language (‘destiny’ is synonym of ‘fate’).